2023
DOI: 10.3389/fmed.2023.1124697
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between inflammatory marker and lipid metabolism in patients with uterine leiomyomas

Abstract: IntroductionObesity is a risk factor for the development of uterine leiomyoma (UL), and the inflammatory response plays a key role in the pathogenesis of UL. Our objective was to assess whether there was an independent relationship between inflammatory markers and triglycerides (TG) in patients with UL.Methods1,477 UL participants who were hospitalized at the Jining Medical University between January 2016 and December 2022 were included in this cross-sectional study. The independent and dependent variables mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In contrast, Mahemuti et al found a notable positive correlation between SII and hyperlipidemia (Mahemuti et al, 2023). In a separate study involving uterine leiomyoma patients, the neutrophil-lymphocyte ratio and SII exhibited a significant positive correlation with TG, while the monocyte-lymphocyte ratio demonstrated a notable negative correlation with TG (Duan et al, 2023). Discrepancies in these study outcomes may arise from variations in the studied populations and the utilization of different indicators.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, Mahemuti et al found a notable positive correlation between SII and hyperlipidemia (Mahemuti et al, 2023). In a separate study involving uterine leiomyoma patients, the neutrophil-lymphocyte ratio and SII exhibited a significant positive correlation with TG, while the monocyte-lymphocyte ratio demonstrated a notable negative correlation with TG (Duan et al, 2023). Discrepancies in these study outcomes may arise from variations in the studied populations and the utilization of different indicators.…”
Section: Discussionmentioning
confidence: 83%
“…Adipokines, adipocyte-released signaling molecules, may promote fibroid tumor proliferation via inflammatory pathways that are upregulated in obese patients [ 6 ]. Among patients with fibroids, pro-inflammatory cytokines and the neutrophil–lymphocyte ratio have been shown to correlate positively with triglyceride levels, suggesting that dyslipidemia, known to induce a pro-inflammatory milieu, may contribute to fibroid growth and development [ 7 ]. The local oxidative stress that accompanies the obese state may further drive fibroid growth via genomic oxidation at the MED12 locus, which is fueled by NOX4 and TGF-β3 signaling [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%